Carbon taxes on consumption: Distributional implications for a just transition in the EU - Sofía Maier; Silvia De Poli; Antonio F. Amores (European Commission, Joint Research Centre (JRC), 2024)
Carbon taxes on household consumption can simultaneously increase public funding and promote greener consumption habits, an appealing combination for the just transition plans of the European Union (EU). However, concerns about equity and public support pose challenges. This paper assesses the distributional and budgetary effects of various designs for an EU-wide hypothetical carbon tax on households consumption. To this end, we extend the EU tax-benefit microsimulation model, EUROMOD, with greenhouse gas (GHG) emissions data from input-output tables and estimate households' carbon footprints. We show that a carbon tax on households GHG emissions would be regressive, thereby inequality-increasing. This is primarily due to the low income elasticity of highly GHG-intense necessity goods, such as food and heating, which represent larger shares of income at the bottom of the distribution. Still, we demonstrate that this inequality-increasing impact can be offset with compensatory cash transfers (though these may be challenging to implement), and at least partially reverted with more progressive (and presumably feasible) tax designs, including rate differentiation by products and tax allowances.
Keywords: H23; Q52; D31; C67; 330; Progressive carbon tax; Just transition; Footprints; Inequality; European Union